Development of Novel Tetracycline and Ciprofloxacin Loaded Silver Doped Hydroxyapatite Suspensions for Biomedical Applications - Daniela Predoi; Simona-Liliana Iconaru; Mihai-Valentin Predoi; Nicolas Buton (MDPI AG, 2022)
The objective of this study consisted of the development of new materials with antimicrobial properties at the nanometric scale that could lead to an increase in therapeutic efficacy and reduction of toxic side effects. This work focuses on obtaining and characterizing stable suspensions with narrow size distribution with antimicrobial properties. The stability of the suspensions obtained by an adapted co-precipitation method was evaluated by ultrasonic measurements. The size and size distribution of the particle populations were determined using scanning electron microscopy (SEM), and dynamic light scattering (DLS). Both methods of analysis showed a narrow distribution of particles. DLS gave a monomodal distribution with hydrodynamic diameters around 38 nm for ciprofloxacin embedded in silver doped hydroxyapatite (AgHA-C) and 45.7 nm for tetracycline embedded in silver doped hydroxyapatite (AgHA-T). The average diameters calculated from SEM were 17 nm for AgHA-C and 19 nm for AgHA-T. Both Ciprofloxacin and Tetracycline influenced the hydroxyapatite structure, which led to the appearance of new vibrational bands characteristic of the specific chemical composition in the FTIR spectrum. The antimicrobial properties of the AgHA-C and AgHA-T suspensions were assessed using the most common reference microbial strains Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Candida albicans ATCC 10231. The results of the in vitro antimicrobial assays determined that the AgHA-C and AgHA-T suspensions exhibited exceptional antimicrobial activity. Moreover, the data revealed that the antimicrobial activity increased with the increase of the incubation time.